Dėl vadinamųjų kokybinių (k)-oks, (k)-oki(a) tipo įvardžių darybos ir raidos - Rosinas, Albertas (Baltistica, 2008)
On the formation and evolution of qualitative (k)-oks, (k)-oki(a)-type pronouns On the basis of data from old Lithuanian writings and existing dialects, an assumption is made that the qualitative (k)-oks, (k)-oki(a)-type pronouns, which formed in the Lithuanian protolanguage, were derivatives of the suffix *-āk- with the stems *šia-, *ja-, *ana, *ta-, *kita-, *ka-, *vę̄na- and *visa-. The masculine and neuter pronouns of this type possessed an a-stem, whereas the feminine pronouns possessed an ā-stem. Some modifications had already occurred in the stems and the declension of the said pronouns in the majority of cases under the influence of *(j)is, *(j)ī́ resp. *patis, *patī́-type pronominal declension even before Leskien’s Law. The most favourable conditions for this change, however, were in the paradigms of the indirect demonstrative pronouns *tākā patī́ and *tākas patis, with the pronoun patis gradually acquiring some ia-stem forms; *tākī́ developed on the model of *patī́, while *tākis > tokis developed on the model of patis (also cf. (j)is, šis) from *tākas. With the modification of the inflectional classes, these feminine pronouns began to be declined as *patī́-type words, whereas their masculine counterparts as (j)is, šis resp. patis pronouns, which possessed the nominative, accusative and inessive i-stem forms; the forms of the other cases possessed an i̯a-stem. The evolution of its further development involved the abolition of the weak suppletion from the paradigms of the feminine and the masculine pronouns (toki → tokia, tokis → tokias), and the reduction of the number of allomorphs according to he model of the adjectives žalias, žalia. This change, however, was not all-encompassing; it had a greater effect on the feminine gender paradigms.